Triacylglycerols and Fatty Acid Compositions of Cucumber, Tomato, Pumpkin, and Carrot Seed Oils by Ultra-Performance Convergence Chromatography Combined with Quadrupole Time-of-Flight Mass Spectrometry - Yanfang Li; Fanghao Yuan; Yanbei Wu; Yaqiong Zhang; Boyan Gao; Liangli Yu (Foods, 2020)
The triacylglycerol (TAG) compositions of cucumber, tomato, pumpkin, and carrot seed oils were analyzed using ultra-performance convergence chromatography (UPC2) combined with quadrupole time-of-flight mass spectrometry (Q-TOF MS). A total of 36, 42, 39, and 27 different TAGs were characterized based on their Q-TOF MS accurate molecular weight and MS2 fragment ion profiles in the cucumber, tomato, pumpkin, and carrot seed oils, respectively. Generally, different vegetable seed oils had different TAGs compositions. Among the identified fatty acids, linoleic acid was the most abundant fatty acid in cucumber, tomato, and pumpkin seed oils and the second most abundant in carrot seed oil with relative concentrations of 54.48, 48.69, 45.10, and 15.92 g/100 g total fatty acids, respectively. Oleic acid has the highest concentration in carrot seed oil and the second highest in cucumber, tomato, and pumpkin seed oils, with relative concentrations of 78.97, 18.57, 27.16, and 33.39 g/100 g total fatty acids, respectively. The chemical compositions of TAGs and fatty acids could promote understanding about the chemical profiles of certain vegetable seed oils, thus improving the potential ability to select appropriate oils with specific functions and a high nutritional value and then develop functional foods in the future.